Encouraging MSME Growth by Improving Financial Literature and Financial Inclusion in Sanur Kauh Village Community - Ni Nyoman Sudiyani; Ni Putu Yuliana Ria Sawitri; I Gusti Agung Prabandari Tri Putri; Cokorda Istri Agung Vera Nindia Putri; Made Ayu Desy Geriadi (International Journal of Social Service and Research, 2022)
Financial literacy has become a hotly discussed issue in recent years in Indonesia. The issues that arise cannot be separated from various polemics that have occurred, ranging from the Asean Economic Community (MEA) to the economic crisis that hit Indonesia in 1998. At this time financial literacy is an important thing and a necessity for the wider community, the public is required to know and understand financial literacy. The low level of public knowledge about the financial industry and its products causes people to be easily trapped in making investments that offer lucrative returns in the short term without considering the risks. This causes harm to the community itself. The government and financial institutions need to seek an understanding of financial literacy for the Indonesian people. One of the efforts to increase financial literacy is education related to legal investment through Community Service conducted by the Faculty of Economics and Business, Ngurah Rai University together with the Regional VIII Bali and Nusa Tenggara Financial Services Authority and the Bali Regional Development Bank for the community of Sanur Kauh Village.